A new variety of fern from Borneo, Sphaerostephanos unitus var. dimorphophylla (Thelypteridaceae) - Takeo Hayashi; Monica Suleiman; Hiroshi Okada; Hirokazu Tsukaya (Magnolia Press, 2018)
The genus Sphaerostephanos is a sub-group of Thelypteridaceae. We collected an undescribed taxon of this genus in Imbak Canyon, Sabah, Borneo. We describe this specimen as a new variety with a drawing and key of this genus.